Transforming kitab kuning literacy in the digital era: Challenges and future prospects for Islamic education - Azwar Sani; Muhammad Kashif Majeed (UIN Kiai Haji Achmad Siddiq Jember, 2025)
Digital transformation has confronted Indonesian Islamic boarding school (pesantren) with the need to redefine traditional Islamic textbook literacy (kitab kuning), marking a critical point in contemporary Islamic education. Although previous studies have addressed institutional and curriculum modernisation, research mapping how these changes reconfigure kitab kuning literacy as a holistic epistemic practice remains limited. Through an integrative literature review, this article synthesises discourse on pesantren modernisation, digital pedagogy, and critical literacy. The findings reveal the transformation of kitab kuning literacy as a three-dimensional construct: (1) traditional literacy (preserving textual authority); (2) digital literacy (enabling access and hybrid learning); and (3) critical literacy (fostering evaluative reasoning in the post-truth era). The main challenge lies in the structural dilemma between expanding access and safeguarding ethical-epistemic integrity, alongside institutional responses ranging from cautious adoption to selective integration. The prospects of Islamic education depend on developing a supporting institutional ecosystem, including governance, dialogic pedagogy, and a selective institutional culture, capable of operationalising this trilogy of literacy sustainably. This article formulates strategic implications for curriculum redesign, teacher training, and digital governance that preserve the knowledge transmission (sanad) tradition while strengthening critical-digital competencies.